Gastric Carcinoma New Insights into Current Management - Laz?r, Daniela (IntechOpen, 2013)
Gastric cancer is the second most common cause of cancer-related death in the world. There are no screening tests available for its diagnosis, therefore patients usually presents in late stages, associated with poor prognosis. Currently, many efforts are made toward new advances in the treatment strategies. The book makes an insight into the assessment of premalignant lesions, current management of early gastric cancer, risk and protective factors in gastric carcinogenesis. "Gastric cancer" provides a detailed description of the morphologic classification, molecular changes and epigenetic alterations of this tumor. The book describes the role of different diagnostic tools in the preoperative assessment of patients and the most important factors contributing to the prognosis. Moreover, it describes the current surgical and chemotherapeutic options for gastric neoplasm. This publication may open new and interesting gates for further research concerning carcinogenesis, genetic and epigenetic alterations, signaling pathways, H. pylori infection, the discovery of protective factors against gastric cancer and of revolutionary therapies of this tumor.